Peripheral refraction profiles in subjects with low foveal refractive errors. - Tabernero, J; Ohlendorf, A; Fischer, M; Bruckmann, A; Schiefer, U; Schaeffel, F (2011)
PURPOSE: To study the variability of peripheral refraction in a population of 43 subjects with low foveal refractive errors. METHODS: A scan of the refractive error in the vertical pupil meridian of the right eye of 43 subjects (age range, 18 to 80 years, foveal spherical equivalent, < ± 2.5 diopter) over the central ± 45° of the visual field was performed using a recently developed angular scanning photorefractor. Refraction profiles across the visual field were fitted with four different models: (1) "flat model" (refractions about constant across the visual field), (2) "parabolic model" (refractions follow about a parabolic function), (3) "bi-linear model" (linear change of refractions with eccentricity from the fovea to the periphery), and (4) "box model" ("flat" central area with a linear change in refraction from a certain peripheral angle). Based on the minimal residuals of each fit, the subjects were classified into one of the four models. RESULTS: The "box model" accurately described the peripheral refractions in about 50% of the subjects. Peripheral refractions in six subjects were better characterized by a "linear model," in eight subjects by a "flat model," and in eight by the "parabolic model." Even after assignment to one of the models, the variability remained strikingly large, ranging from -0.75 to 6 diopter in the temporal retina at 45° eccentricity. CONCLUSIONS: The most common peripheral refraction profile (observed in nearly 50% of our population) was best described by the "box model." The high variability among subjects may limit attempts to reduce myopia progression with a uniform lens design and may rather call for a customized approach.